2021
DOI: 10.1155/2021/8928509
|View full text |Cite
|
Sign up to set email alerts
|

miR-193a-3p Promotes the Invasion, Migration, and Mesenchymal Transition in Glioma through Regulating BTRC

Abstract: Background. The present study is aimed at exploring the specific expression of miR-193a-3p and the mechanism underlying miR-193a-3p-mediated mesenchymal transition (MT), invasion, and migration in glioma. Methods. The gene expression profile datasets of GSE39486 and GSE25676 were downloaded from the National Center for Biotechnology (NCBI). Data regarding the expression of miR-193a-3p and survival curves were derived from Chinese Glioma Genome Atlas (CGGA). Online websites including miRWalk, DIANA, and starbas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…As expected, the expression of miR-193a was lower in GC tissues than that in the corresponding peritumoral normal tissues (P < 0.05) (Figure 1(a)). According to the median level of miR-193a, patients were divided into a low expression group and a high expression group [20]. Results showed that high expression of miR-193a was associated with poor prognosis in gastric cancer (P < 0.05) (Figure 1(b)).…”
Section: Downregulation Of Mir-193a Predicts Poor Prognosis Ofmentioning
confidence: 99%
“…As expected, the expression of miR-193a was lower in GC tissues than that in the corresponding peritumoral normal tissues (P < 0.05) (Figure 1(a)). According to the median level of miR-193a, patients were divided into a low expression group and a high expression group [20]. Results showed that high expression of miR-193a was associated with poor prognosis in gastric cancer (P < 0.05) (Figure 1(b)).…”
Section: Downregulation Of Mir-193a Predicts Poor Prognosis Ofmentioning
confidence: 99%
“…To better understand the protein-protein interactions among the differentially expressed proteins of each group, we constructed protein-protein interaction (PPI) networks through Omicsbean. Proteins were then grouped based on their GO annotations with p-value < 0.05 [19].…”
Section: Tunel Assaymentioning
confidence: 99%
“…MiRNAs are noncoding RNAs that can inhibit the expression of RNA through translation inhibition or messenger RNA degradation. 42 , 43 In recent years, studies have revealed that some miRNAs could be regulators of immune and inflammatory responses and are potential therapeutic targets in DN. 15 , 16 Single nucleotide polymorphisms of miRNA-related genes can affect the production, expression, and function of mature miRNAs, thus affecting disease susceptibility and the immune response.…”
Section: Discussionmentioning
confidence: 99%